Proposal to link the school library of the Centro Educativo Unidad Pedagógica de Cuatro Reinas with the children's room of the Francisco J. Orlich Public Library in the canton of Tibás, Heredia, Costa Rica. - Espinoza Baltodano, Sandra (2011)
This document is a summary of the final graduation work on the current situation of two libraries: the school library of the Centro Educativo Unidad Pedagógica de Cuatro Reinas and the children's room of the Francisco J. Orlich Public Library located in the canton of Tibas. The results obtained from the diagnosis of the two information units mentioned above are presented, then the strategies for linking the two libraries are presented and finally the conclusions appear.